Pengaruh Ulasan pada Minat Berkunjung: Peran Mediasi Persepsi pada Situs Web - Indra Nur Wicaksana; Harmanda Berima Putra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of reviews on visiting interest through perception as a mediating factor in the context of a website. The research involved 170 respondents who intended to visit a tourist destination and had previously viewed at least one review from a tourism website. Structural analysis results indicate that reviews have a positive influence on visiting interest, reviews positively affect perception, perception positively influences visiting interest, and perception successfully mediates the relationship between reviews and visiting interest.